2020
DOI: 10.1093/nar/gkaa129
|View full text |Cite
|
Sign up to set email alerts
|

The critical function of the plastid rRNA methyltransferase, CMAL, in ribosome biogenesis and plant development

Abstract: Methylation of nucleotides in ribosomal RNAs (rRNAs) is a ubiquitous feature that occurs in all living organisms. The formation of methylated nucleotides is performed by a variety of RNA-methyltransferases. Chloroplasts of plant cells result from an endosymbiotic event and possess their own genome and ribosomes. However, enzymes responsible for rRNA methylation and the function of modified nucleotides in chloroplasts remain to be determined. Here, we identified an rRNA methyltransferase, CMAL (Chloroplast MraW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(44 citation statements)
references
References 96 publications
3
39
2
Order By: Relevance
“…To firmly establish the in vivo function of mTERF9, we performed a comprehensive analysis of the in vivo RNA and protein interaction networks of mTERF9. Our co-immunoprecipitation results demonstrated that mTERF9 binds to the 16S rRNA in chloroplasts as well as ribosomal proteins, CPN60 chaperonins and known auxiliary ribosomal factors involved in rRNA processing such as the MraW-like 16S rRNA methyltransferase (CMAL) ( 68 ), YbeY endoribonuclease ( 67 ), RNase J ( 50 ), RNase E-like protein (RHON1) ( 51 ) or DEAD/DEAH-box RNA helicases (RH3 and ISE2) ( 47–49 ). The fractionation of chloroplast high-molecular-weight protein complexes combined with the comparative mTERF9 protein interactome in presence or absence of RNase together with the 16S rRNA mTERF9 co-immunoprecipitation indicate that mTERF9 preferentially associates with the 30S small ribosome subunit in vivo .…”
Section: Discussionmentioning
confidence: 94%
“…To firmly establish the in vivo function of mTERF9, we performed a comprehensive analysis of the in vivo RNA and protein interaction networks of mTERF9. Our co-immunoprecipitation results demonstrated that mTERF9 binds to the 16S rRNA in chloroplasts as well as ribosomal proteins, CPN60 chaperonins and known auxiliary ribosomal factors involved in rRNA processing such as the MraW-like 16S rRNA methyltransferase (CMAL) ( 68 ), YbeY endoribonuclease ( 67 ), RNase J ( 50 ), RNase E-like protein (RHON1) ( 51 ) or DEAD/DEAH-box RNA helicases (RH3 and ISE2) ( 47–49 ). The fractionation of chloroplast high-molecular-weight protein complexes combined with the comparative mTERF9 protein interactome in presence or absence of RNase together with the 16S rRNA mTERF9 co-immunoprecipitation indicate that mTERF9 preferentially associates with the 30S small ribosome subunit in vivo .…”
Section: Discussionmentioning
confidence: 94%
“…CMAL contains a 41 amino acid‐long putative chloroplast transit peptide at the N‐terminus, and the chloroplast localization of CMAL has recently been demonstrated (Zou et al, 2020). The transient expression of the CMAL‐GFP (green fluorescent protein) fusion protein in tobacco leaves further confirmed that the nucleus‐encoded CMAL protein is localized to the chloroplasts (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…These growth and developmental defects of the cmal mutant might be attributed to deficiencies in chloroplast biogenesis and function. A recent study demonstrated that the structures of the cmal mutant chloroplasts are abnormal and the photosynthetic activity of the cmal mutant is lower than that of the wild type (Zou et al, 2020). Moreover, our data indicate that the cmal mutant does not develop true green leaves on sucrose‐deficient medium, and this defect can be recovered by adding sucrose to the medium (Figure 2D).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with that, the stability of several isoforms of the 23S rRNA resulting from the hidden breaks processing were impaired in mterf9. Several auxiliary factors involved in chloroplast ribosomal assembly have been recently characterized and the majority of these are bacterial homologs or harbor RNA binding domains that are conserved in bacteria (47)(48)(49)(50)(51)55,(68)(69)(70). Without any surprise, these protein homologs perform conserved functions in rRNA processing and therefore, ribosome assembly in chloroplasts.…”
Section: Discussion Mterf9 Assists Chloroplast Ribosome Assembly Via mentioning
confidence: 99%